VARIASI POHON FRAKTAL MENGGUNAKAN L-SYSTEMS - Ramdhan, Pradifta Gilang; Purnomo, Kosala D.; Ubaidillah, Firdaus (Majalah Ilmiah Matematika dan Statistika, 2021)
Fractal tree is simply a trunk and a number of branches, each of which looks like the tree itself. The fractal tree can be generated using the IFS and L-Systems methods. In this article, the author develops fractal tree generation using L-Systems with additional variations. The variations given are in thickness, length, and branch angle. This development is expected to produce more diverse fractal tree patterns. In generating a fractal tree using L-Systems, it begins by determining the letters and symbols to be used. Then determine which axioms should be used. Then the production rules are made together with the determination of the parametric L-Systems. And the last is to determine the probability value for the stochastic L-Systems. In the deterministic L-Systems, thickness variations, length variations, and branch angle variations are carried out. In the variation of branch thickness, if the ratio of the thickness of the left branch is greater than that of the right branch, the fractal tree is skewed to the left. Then in the variation of branch length if the ratio of the length of the left branch is smaller than the ratio of the length of the right branch, the length of the left branch is longer than the length of the right branch. Then at the angle of the branching the smaller the ???? that is included causes the branches to be closer together. The use of stochastic L-Systems can produce more diverse fractal tree patterns, even though they use the same production rules and parameter values